Flexible and Stretchable Electronic Composites - Ponnamma, Deepalekshmi; Sadasivuni, Kishor Kumar; Wan, Chaoying; Thomas, Sabu.; Al-Ali AlMa'adeed, Mariam; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is the first comprehensive collection of electronic aspects of different kinds of elastomer composites, including combinations of synthetic, natural and thermoplastic elastomers with different conducting fillers like metal nanoparticles, carbon nanotubes, or graphenes, and many more. It covers elastomer composites, which are useful in electronic applications, including chemical and physical as well as material science aspects. The presented elastomer composites have great potential for solving emerging new material application requirements, for example as flexible and wearable electronics. The book is structured and organized by the rubber/elastomer type: each chapter describes a different elastomer matrix and its composites. While introducing to important fundamentals, it is application-oriented, discussing the current issues and challenges in the field of elastomer composites. This book will thus appeal to researchers and scientists, to engineers and technologists, but also to graduate students, working on elastomer composites, or on electronics engineering with the composites, providing the readers with a sound introduction to the field and solutions to both fundamental and applied problems.
From the Contents: Introduction -- Natural Rubber (NR) and its composites -- Polyurethane (PU) and its composites -- Isobutylene Isoprene Rubber (IIR) and its composites -- Nitrile Butadiene Rubber (NBR) and its composites.
Keywords: Polymers; Nanotechnology; Microtechnology; Microelectromechanical systems; Nanochemistry; Optical materials; Nanoscience; Polymers; Nanotechnology; Microsystems and MEMS; Nanochemistry; Optical Materials; Nanophysics